2017
DOI: 10.1186/s13023-017-0641-1
|View full text |Cite
|
Sign up to set email alerts
|

Not only dominant, not only optic atrophy: expanding the clinical spectrum associated with OPA1 mutations

Abstract: BackgroundHeterozygous mutations in OPA1 are a common cause of autosomal dominant optic atrophy, sometimes associated with extra-ocular manifestations. Few cases harboring compound heterozygous OPA1 mutations have been described manifesting complex neurodegenerative disorders in addition to optic atrophy.ResultsWe report here three patients: one boy showing an early-onset mitochondrial disorder with hypotonia, ataxia and neuropathy that was severely progressive, leading to early death because of multiorgan fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 28 publications
0
29
0
1
Order By: Relevance
“…Similarly, areas of reduced immunoreactivity were observed using the TOMM20 antibody confirming impairment of the mitochondrial network distribution (right panel). These abnormalities were not detected in the muscle biopsy of a patient with biallelic mutations in OPA1 (last bottom row) already described (Nasca, Rizza et al, ). The plasma membrane is stained in red fluorescence with an antibody against dystrophin [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…Similarly, areas of reduced immunoreactivity were observed using the TOMM20 antibody confirming impairment of the mitochondrial network distribution (right panel). These abnormalities were not detected in the muscle biopsy of a patient with biallelic mutations in OPA1 (last bottom row) already described (Nasca, Rizza et al, ). The plasma membrane is stained in red fluorescence with an antibody against dystrophin [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 49%
“…Histochemistry of the muscle sample of a patient harboring compound heterozygous mutations in OPA1 (Nasca, Rizza et al, ) was studied and compared with those of DNM1L patients and showed no patchy staining abnormalities (Figure lowest panel). In addition, by Long Range PCR we also searched comparatively for multiple deletions in muscle samples and found multiple deletions only in the OPA1 mutated patient and not in the DNM1L patients (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Human COQ5 performs much better in yeast when its presequence is substituted by the yeast one (Nguyen et al., ). In the case of OPA1 , complementation was also achieved using hybrid constructs, which included the MTS and the transmembrane domain (Nasca et al., ; Nolli et al., ). In all these cases, these genes are considered orthologs of the yeast gene.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Notably, compound heterozygous OPA1 mutations have been described in a few cases manifesting complex neurological involvement in addition to optic atrophy. 13,17,18 About 30% of DOA patients, however, do not carry OPA1 mutations. Heterozygous mutations in a second gene, associated with DOA and cataracts and/or deafness, affect the OPA3 gene, 19,20 known for the recessive Costeff syndrome (Online Mendelian Inheritance in Man database [OMIM] #258501).…”
Section: Introductionmentioning
confidence: 99%